Assessment on the growth performance of planted Dryobalanops beccarii at reforestation sites after implementation of selective girdling - Mohd Effendi Wasli; Douglas Bungan Ambun; Meekiong Kalu; Mogeret Sidi; Hafsah Nahrawi; Hashimah Elias (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wasli ME, Ambun DB, Kalu M, Sidi M, Nahrawi H, Elias H. 2020. Assessment on the growth performance of planted Dryobalanops beccarii at reforestation sites after implementation of selective girdling. Biodiversitas 21: 1880-1889. This study was conducted to evaluate the growth performance of planted Dryobalanops beccarii Dyer at reforestation sites after silvicultural practices in Gunung Apeng National Park (GANP), Sarawak. The assessed area was planted with D. beccarii in 2005 and undergo silvicultural treatment by understory clearing which implemented annually. Due to the suppressed growth rate of the planted trees, an additional silvicultural treatment, the selective girdling on selected pioneer species, was implemented once, in 2012. In this study, study plots with two treatments were established: T1: understory clearing only (control plot), and T2: additional selective girdling of existing pioneer species in addition to the understory clearing practice applied in T1. The growth performance of the planted D. beccarii in terms of DBH, height, survival and mean annual increments in diameter (MaiD) and height (MaiH) were assessed and monitored at the initial stage when the selective girdling treatment was applied and 4, 24, 36, 48, 60 and 72 months after girdling. Our findings showed that the survival rates of planted trees at 72 months under treatments T1 and T2 were 82.9% and 79.2%, respectively. The average tree DBH in T2 was significantly higher than that in T1, and the average tree DBH values for T1 and T2 were 7.5 cm and 9.4 cm, respectively. The average tree heights for T1 and T2 were 8.3 m and 9.2 m, respectively. In terms of the mean annual increments in height (MaiH) and diameter (MaiD), those in T2 were significantly higher than those in T1. Our findings indicated that T2 started to show better growth performance than T1 after a period of 36 months. In conclusion, the additional silvicultural treatment by selective girdling at the reforestation site had a long-term, progressive effect on the growth performance of the planted trees.